The bankers' new clothes : what's wrong with banking and what to do about it - Admati, Anat R. (Princeton University Press, 2013)
What is wrong with today's banking system? The past few years have shown that risks in banking can impose significant costs on the economy. Many claim, however, that a safer banking system would require sacrificing lending and economic growth. The Bankers' New Clothes examines this claim and the narratives used by bankers, politicians, and regulators to rationalize the lack of reform, exposing them as invalid. Admati and Hellwig argue we can have a safer and healthier banking system without sacrificing any of the benefits of the system, and at essentially no cost to society. T.